TRPM2 Plays a Minor Role in AKI and Kidney Fibrosis. Issue 1 (27th January 2022) - Kurata, Yu; Tanaka, Tetsuhiro; Cernecka, Hana; Eitner, Frank; Nangaku, Masaomi
Key Points: TRPM2 is a Ca2 + -permeable cationic channel and serves as an oxidative stress sensor. TRPM2 deletion was harmful in renal ischemia-reperfusion injury, whereas TRPM2 deletion mitigated kidney fibrosis. Our findings suggest the role of TRPM2 in kidney diseases is context dependent.